COLLABORATIVE AND PROBLEM-BASED LEARNING IN PROMOTING INDONESIAN EFL LEARNERS’ LEARNING AUTONOMY - Kristian Florensio Wijaya (Polyglot, 2021)
There is an indispensable need for language teachers to promote a more specific breakthrough in diverse wide-ranging Indonesian EFL classroom contexts. One of the efficient teaching-learning strategies worthwhile to achieve this holistic educational major objectivity is to promote student-centered learning approaches in which all learners are capable of constructing a vast array of knowledge jointly with their trusted learning companions. Responding to the resurgence of this learning strategy, both collaborative and problem-based learning enterprises can potentially breed more proficient, critical, creative, and autonomous L2 academicians. These positive matters may be due to the considerable number of precious learning opportunities imparted for learners to enrich each other’s existent understanding in the light of meaningful sharing as well as intimate cooperative networking. This study was conducted by using a library approach to reveal the renewable findings out of the observed phenomenon. Thus, 30 collaborative along with problem-based learning studies conducted in Indonesian EFL learning contexts were overviewed in this study. Generally speaking, two specific major themes strongly suggested Indonesian EFL teachers incorporating collaborative and problem-based learning approaches in their multiverse second language classroom settings to promote more fruitful learning outcomes that suit learners’ real-time life experiences.BAHASA INDONESIA ABSTRACT: Ada sebuah kebutuhan yang sangat krusial bagi para guru Bahasa untuk membawa sebuah terobosan yang spesifik di dalam keanekaragaman pembelajaran Bahasa Inggris konteks negara Indonesia. Salah satu dari strategi pembelajaran yang efektif untuk mewujudkan nilai holistik pendidikan ini adalah menerapkan metode pembelajaran berbasis student-centered dimana semua pelajar dapat memperkaya diri mereka dengan berbagai macam pengetahuan bersama-sama dengan rekan-rekan pembelajaran yang dipercaya. Berkenaan dengan kebangkitan dari strategi pembelajaran ini, pembelajaran berbasis kolaboratif serta pemecahan masalah berpeluang menghasilkan cendekiawan Bahasa kedua yang lebih cakap, kritis, kreatif, dan mandiri. Hal-hal positif dari pembelajaran ini barangkali disebabkan oleh banyaknya ketersediaan dari kesempatan belajar yang berharga ditujukan kepada para pelajar untuk memperkaya pemahaman mendasar mereka satu sama lainnya melalui sharing yang bermanfaat dan kerjasama kooperatif yang intim. Penelitian kualitatif ini menerapkan metode studi pustaka dengan meninjau hasil-hasil yang berarti dari 30 penelitian pembelajaran berbasis kolaboratif dan pemecahan masalah. Secara umum, 2 tema utama yang spesifik dengan kuat menganjurkan para guru Bahasa Inggris untuk menerapkan pembelajaran berbasis kolaboratif dan pemecahan masalah didalam konteks pembelajaran Bahasa Inggris yang beraneka ragam untuk mempromosikan pembelajaran yang lebih bermanfaat sesuai dengan konteks kehidupan sehari-hari para pelajar.